Phase Formation during Heat Treatment of Zn‐ and ZnAlMg‐Coated Steels at 400 and 750 °C. Issue 7 (25th March 2019) - Windmann, Matthias; Barthen, Mario; Opitz, Tobias; Hahn, Isabel; Röttger, Arne; Theisen, Werner
Abstract : In contrast to a cold‐forming process, a tempered forming process is able to deform high‐strength steel used for manufacturing automotive bodyworks in a more economic manner. Cold‐formed steel sheets are commonly coated with a Zn or ZnAlMg layer for cathodic corrosion protection. The tempering process would lead to diffusion processes at the steel/coating interface, which is accompanied by the formation of new phases in the coatings. This publication focuses on phase formation in Zn and ZnAlMg coatings on steel sheets, which are heat‐treated at 400 and 750 °C. the authors find that the pure Zn coating remains in the solid state and transforms into the intermetallic δ phase (FeZn10 ) during heat treatment at 400 °C. The coating melts during heating to 750 °C, but remains in the solid state after transformation into the Γ phase (Fe4 Zn9 ) and α‐Fe. In the ZnAlMg coating, minor iron diffusion occurs at a temperature of 400 °C. Within a dwell time of 600 s, intermetallic Fe–Zn phases are not formed. During heat treatment at 750 °C, phase formation in the ZnAlMg coating is very similar to that in the pure Zn coating, during which Γ (Fe4 Zn9 ) and α‐Fe are formed. Abstract : The paper presents the phase formation in Zn‐ and ZnAlMg‐coated steel sheets after heat treatment at 400 and 750 °C for different dwell times. Phase formation is investigated by X‐ray spectroscopy and galvanostatic stripping measurements. Depending on temperature and dwell time different intermetallic Zn–Fe phases are formed in the coating.